Pemanfaatan Virtual Community Sebagai Media Komunikasi E-Bussines - Beny Sitakar; Yudi Fakhrul Rozi; Dini Lestari (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this research is to examine the use of virtual communities as a medium of communication in the context of e-business. The research approach used is descriptive qualitative analysis, which aims to provide an explanation based on existing evidence and consider all aspects that are relevant to the topic discussed. Secondary sources such as books and journals were used to collect information for this study. Data analysis methods used include qualitative analysis and textual analysis.